Strategi Pengembangan Pariwisata Pasca Bencana Tsunami di Kabupaten Lampung Selatan - Sofyan Sofyan; Dian Kagungan; Nana Mulyana (Jurnal Administrativa, 2020)
Lampung is one of the provinces that has a considerable tourism potential in which each region has tourism potential with its own unique attraction in South Lampung regency. However, the Tsunami disaster that struck the coastal areas of Banten and South Lampung on 22 Desemeber 2018, impacted the decline in the number of tourists visiting the archipelago and abroad to tourist destinations by the end of year 2018. Based on the problems raised above, the purpose of this research is to describe and analyze the strategy conducted by the Tourism and culture Office of South Lampung Regency in the effort to develop tourism sector in South Lampung district after Tsunami disaster. This type of research is qualitative research with a descriptive approach. The research informant is determined purpossive. Data collection techniques are conducted with observations, interviews and documentation. Data analysis techniques are carried out with data reduction, data presentation, drawing conclusions and data triangulation. Data is presented and in a descriptive analysis. Based on the results of the research is known that the Tourism and culture Department of South Lampung district has a strategy to develop tourism potential in South Lampung regency. In determining a strategy for tourism development in South Lampung District after the Tsunami disaster pay attention to four basic factors. These four factors are strengths, weaknesses, opportunities and threats with some sectors involved in the tourism development process. The conclusion of this research is based on the SWOT anilisis which produces four strategies i.e. SO strategy, WO Strategy, Strategy ST, and WT strategy